PENENTUAN POTENSI LOKASI ATM (AUTOMATIC TELLER MACHINE) BANK NAGARI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) DI KOTA PADANG - yanti novita; Yudi Antomi (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The purpose of this research is to obtain (1) an overview of the potential determination parameters, (2) the potential area to become locations , and (3) evaluate the existence of an existing Bank Nagari ATM. The research method is descriptive quantitative. The data analysis technique uses the scoring method to determine the distribution patterns and evaluation of the existing ATMs. Data processing used by Geographic Information Systems and Nearest Neighbor Analysis. The results of the study (1) there are that parameters are determination of the potential location of Bank Nagari ATMs in Padang City is, land use, positive accessibility, regularity of settlements, existing ATMs and crime rates. (2) Potential locations of Bank Nagari ATMs in the city of Padang can be classified based on three categories, namely potential I (high) with a value of 21-34 percentage of the area 0.22%. Potential II (moderate) is at a value of 6-20 percentage of the region 20,51%. And for potential III (low) is at a value of (-9) -5 with a regional percentage of 79,26%. And the pattern of ATM location distribution in the study area is included in the clustured pattern with an T index value of 0.72. (3) Evaluation of the decrease in ATM locations there are three classifications, a high decrease with a value of 3-66, a moderate decrease with a value of 67-130, and a low decrease with a value of 68-194.